Pendidikan Kesehatan Pencegahan Depresi pada Warga Binaan Lembaga Pemasyarakatan di Surabaya - Cempaka, Anindya Arum; Lilyana, Maria Theresia Arie (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Correctional Inmates are at risk of experiencing significant depression twice as much as the general population. Because prisoners have psychological vulnerability because of their status as convicts with a negative impression or stigma, the purpose of this community service is as a promotive and preventive effort, especially for correctional inmates in promoting the prevention of depression so that they can achieve optimal mental health. Correctional institutions and WBP are partners in this community service. The method of community service activities is health education or counselling using the lecture method. PowerPoint media was used to support the activity's success while teaching material in leaflets was distributed after the counselling event. The activity ended with the completion of the posttest by the participants to measure the participants understanding. The indicator of the success of this activity is the increase in participants' knowledge about depression prevention. Results of the data analysis showed an influence of health education on depression prevention on the participant's level of knowledge. So it can be concluded that this activity affects the knowledge of participants. When a person receives information, it will affect the level of knowledge. In comparison, knowledge is an essential part of forming one's behaviour. Health education is expected to increase prisoners' knowledge to prevent depression while living in prison.